MNQ derivative D19 alleviates LPS-induced inflammation and oxidative stress in sheep follicular granulosa cells through the GPX4-mediated ferroptosis - Chen, Chunlu; Lu, Jia; Qu, Yuhan; Dong, Jianhua; Hong, Yihao; Ren, Yongping; Jiang, Shouqing; Baptista, Rafael; Wang, Dong; Mur, Luis Aj; Lyu, Lihua (Frontiers in Veterinary Science, 2025)
Introduction2-methoxy-1,4-naphthoquinone (MNQ), a compound derived from Impatiens balsamina L., is recognized for its anti-inflammatory and antioxidant properties. However, the effects of D19, a derivative of MNQ, remain unexplored. This study aimed to elucidate the protective effect of D19 against lipopolysaccharide (LPS)-induced follicular granulosa cells (GCs) dysfunction in sheep and its underlying molecular mechanisms.MethodsAn in vitro model of GCs injury was established using LPS to induce inflammation and oxidative stress. The effects of D19 were evaluated by examining inflammatory response, oxidative stress, ferroptosis and steroidogenesis following treatment. Gene interference was applied to knock down GPX4 expression to validate its role in the protective mechanism of D19.ResultsD19 attenuated LPS-induced ferroptosis in GCs by restoring the expression of the key ferroptosis regulator GPX4. Subsequently, interfering with GPX4 activated NF-κB and upregulated the expression of inflammatory factors (TNF-α, IL-1β, IL-6) while disrupting NRF2 and inhibiting the expression of antioxidant-related factors (CAT, GSH-PX, SOD2). D19 effectively protected GCs from GPX4 deficiency-induced inflammation and oxidative damage. Furthermore, D19 mitigated ferroptosis caused by GPX4 deficiency and maintained iron metabolic homeostasis by restoring the morphology of GCs, increasing mitochondrial membrane potential, decreasing the accumulation of Fe2+ and lipid peroxides, and promoting the expression of GPX4 and FTH1. D19 also improved steroid hormone secretion abnormalities caused by GPX4 deficiency.DiscussionThese results demonstrate that D19 protects sheep follicular GCs from LPS-induced damage by modulating the GPX4-mediated ferroptosis signaling pathway, providing new potential drugs and therapeutic targets for addressing GCs dysfunction and follicular developmental abnormalities.